STUDI PEMODELAN VARIASI DIMENSI PILAR TERHADAP GEOMORFOLOGI SUNGAI - Iman Muhardiono (LPPM Universitas Negeri Jakarta, 2023)
The behavior of river flow patterns on the condition of the pillar dimensions can affect the geomorphology conditions of the river, namely the unbalanced local scouring between sediment transport and sediment supply so that it will affect the strength of the pillar. This study aims to study the effect of pillar dimensions on scour depth and channel base changes in the pillar area. The method of observation was carried out by simulations using Nays2DH with the same parameters for each test of each dimension with discharge (Q) = 0.5 m3/s, sediment diameter (D50) = 0.35 mm, channel width (B) = 5 m, channel length (L) = 25 m, slope (i) = 0.005 and drainage time (t) = 7200 s. The simulation results show the basic scour pattern of the channel which has the smallest value, the diamond type pillar. Degradation - Basic channel agitation on diamond type pillars, showing a pattern that tends to be evenly distributed compared to semi rounded, rectangle, or octagonal types. Period (t) 7200 s downstream of the pillar, semi rounded type scours change <0.3 m, rectangle type scours changes <0.4 m, octagonal type scours changes <0.4 m, and diamond type scours changes <0.2 m. So the dimensions of the diamond type are more effective in reducing the depth of scour.